Significados atribuídos por professores a ‘protagonismo’ em projetos de igualdade de direitos voltados à diversidade sexual - (:unkn) unknown (Universidade Federal do Amazonas, 2013)
This research purpose to identify and analyze meanings attributed by teachers to `protagonism` in projects of equality of rights toward sexual diversity. Because it is understood that the teacher can act in a development zone mediating equality speeches between the school community, he can promote social transformation becoming transversal themes related to sexuality on a systhematized form, founded by the scientific knowledge. It was taken as general objective: Comprehend the meanings attributed by the teachers to the protagonism in the construction and execution of equality of rights toward the sexual diversity at school. The specific objectives are: identify the attributions of meanings about the Projects of Equality of Rights by LGBT students and their articulation with the protagonism of the teachers; comprehend the attributions of meanings of protagonism for minimalize the prejudices for LGBT students among teachers and discuss the attributions of meanings about the motivations that turn the teacher into a protagonist in projects of equality of rights to LGBT students. It was adopted a view of man proposed by Vigotski, that refers to the human development through a socio-historical presupposition. The research assumed a qualitative approach of exploratory character. Participated of the research 06 teachers, that work at high school. It had been accomplished semi-structured interviews for data collecting. Subsequently it was created a corpus of analysis and it was used the technique of analysis denominated nucleus of signification. The data are articulated in three chapters, according to the specific objectives of the research, resulting in a total of 05 nucleus of signification. In the first chapter it is pointed two nucleus: um, whereat, the teachers consider that accomplish project in a forced manner is not nice because the education has to evolve affective entailment and, shouldn’t be permeated by obligation and, other nucleus attribute to the school a “non-place” to the sexual diversity taking out the possibilities of new productions of meanings and the resignification in the process of education to the diversity. On the second chapter, it is presented a nucleus which is guided on the protagonism of the teacher for the minimization of prejudices, the nucleus is centralized on the class discussion about the thematic and at the third chapter it forms two more nucleus: the first refers to what motivates the teacher to work for the diversity on the perspective of thought changing related to the LGBT people and the second nucleus is related to what doesn’t motive entailed to the religious question or working overload. Therefore, it is important to consider that there is interest and that some look for taking the theme of sexual diversity to the classroom, but, it is still absent, the speech founded on the idea of equality of rights. The data are positive for reaching the equalitarian realities. It features that the teachers consider themselves as key people to immerge knowledges and foment equalitarian speeches. It is very positive and it has interfaces in which the purpose of equality of rights is based. The results obtained can be considered as satisfactory for the research, because these professionals, inserted on the education, demonstrate accessibility to obtain new knowledges and interest for pursuit the formation, respecting the other and adjusting to the context of the natural manifestations of human beings, although still are evolved by antagonistic feelings of knowing and doing.
Keywords: Significados; Protagonismo; Projetos de Igualdade de direitos; Professores; Diversidade sexual; Educação; Meanings; Protagonism; Projects of equality of rights; Sexual diversity; CIÊNCIAS HUMANAS: PSICOLOGIA